Features of the Organization of Accounting on Farms of Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Farmers have a number of peculiarities in the formation of funds, capital, in the distribution of results, in the system of management and organization of accounting and control. Accounting in farms can not be carried out in the uniform form, as the subjects differ in size of land, specialization, production facilities and sales proceeds from sales; therefore, it is necessary to introduce national regulations (standards) that would determine the characteristics of accounting for these farms depending on their Features. The simplest and simplest form of accounting for farms has become most widespread. The production of agricultural products is determined in a variety of ways and conditions of receipt, storage and use of the resulting finished product.
Keywords: farm, production, bookkeeping, simple and simplified form, agriculture, financial result